The Modification of the Runner and Ingate Geometry to eliminate Misrun Defects on the Piston using Gravity Die Casting - Vika Rizkia; Muhammad Fernanda Alvi Yasin; Nabila Banowati; Veronika Noviaty (MBI, 2023)
Piston is an essential component of an engine because it plays a crucial role in the combustion process that drives the motorcycle. Gravity dies casting has become an ideal method for producing pistons owing to its high-quality product, cost-effective with excellent dimensional accuracy, good surface finish, and performance characteristics. However, misrun defect may occur during metal filling and solidification. This study aims to find the suitable dimensions for motorcycle piston products without the presence of misrun using MAGMASoft. The geometry modification introduced in this research are an ingate area of 176, 264, and 352 mm2 as well as the angle of runner of 60, 160, and 180o. Modifying the ingate area to 264 mm2 and the angle of the runner to 160o eliminated the misrun defect in the piston product. This phenomenon results from the laminar flow, higher temperature, and quicker flow velocity of the molten metal as it fills the window (the thinnest part of the piston).